FADS1 rs174550 genotype and high linoleic acid diet modify plasma PUFA phospholipids in a dietary intervention study - Meuronen Topi; Lankinen Maria A.; Kärkkäinen Olli; Laakso Markku; Pihlajamäki Jussi; Hanhineva Kati; Schwab Ursula (SPRINGER HEIDELBERG, 2022)
Introduction Fatty acid desaturase 1 (FADS1) gene encodes for delta-5 desaturase enzyme which is needed in conversion of linoleic acid (LA) to arachidonic acid (AA). Recent studies have shown that response to dietary PUFAs differs between the genotypes in circulating fatty acids. However, interactions between the FADS1 genotype and dietary LA on overall metabolism have not been studied.
Objectives We aimed to examine the interactions of FADS1 rs174550 genotypes (TT and CC) and high-LA diet to identify plasma metabolites that respond differentially to dietary LA according to the FADS1 genotype.
Methods A total of 59 men (TT n = 26, CC n = 33) consumed a sunflower oil supplemented diet for 4 weeks. Daily dose of 30, 40, or 50 ml was calculated based on body mass index. It resulted in 17-28 g of LA on top of the usual daily intake. Fasting plasma samples at the beginning and at the end of the intervention were analyzed with LC-MS/MS non-targeted metabolomics method.
Results At the baseline, the carriers of FADS1 rs174550-TT genotype had higher abundance of long-chain PUFA phospholipids compared to the FADS1 rs174550-CC one. In response to the high-LA diet, LA phospholipids and long-chain acylcarnitines increased and lysophospholipids decreased in fasting plasma similarly in both genotypes. LysoPE (20:4), LysoPC (20:4), and PC (16:0_20:4) decreased and cortisol increased in the carriers of rs174550-CC genotype; however, these genotype-diet interactions were not significant after correction for multiple testing.
Conclusion Our findings show that both FADS1 rs174550 genotype and high-LA diet modify plasma phospholipid composition.